Azania between history and eschatology: Bonganjalo Goba’s Africanist theology - Africa, Obakeng G. (Verbum et ecclesia, 2025)
This article examines Bonganjalo Goba’s theological vision through the lens of Azanian Africanist critique, arguing that his historical awareness fundamentally shapes his theology as an Africanist theology. Goba’s work, particularly Agenda for Black Theology: Hermeneutics for Social Change, foregrounds conquest as the foundational injustice structuring black oppression, positioning black theology within the broader struggle for liberation. The article situates Goba’s theology within the Azanian intellectual tradition, engaging with Joel Modiri’s tenets of Azanian Africanist critique – specifically, the insistence that South Africa is an illegitimate settler-colonial construct requiring fundamental transformation. Central to this argument is Goba’s eschatology, which frames Azania as an eschatological horizon, rejecting Western theological frameworks that defer liberation to an otherworldly realm. Instead, Goba’s theological vision insists on the inseparability of history, faith and the political imperative of black self-determination. By engaging Goba’s theology alongside Azanian thinkers, this study demonstrates that his eschatology is not merely a doctrinal position but an urgent commitment to dismantling settler-colonial structures. In doing so, the article reclaims Goba’s relevance for contemporary black theological discourse, affirming that black theology must remain attuned to the unfinished struggle for liberation and the realisation of Azania as both a theological and political horizon. Intradisciplinary and interdisciplinary implications: This article creates commensurability between Goba’s theology and Azanian Africanist discourse (predominantly in law, political science and philosophy). It calls for rethinking theological reflection in relation to historical consciousness, settler colonialism and the black radical tradition within theological and religious studies.